The Short Term Outcome of Therapeutic Hypothermia Compared with Standard Treatment among Asphyxiated Newborns Presenting after 6 hours of Life - Javed Laal, Zunaira Javaid, Muhammad Anwar, Amjad Iqbal, Ameer Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare the short term outcome of therapeutic hypothermia in asphyxiated newborn with standard treatment presenting after 6 hours of life. Methodology: It was Randomized controlled trial conducted in the department of Pediatric Medicine, Bahawal Victoria Hospital, Bahawalpur from December 2018 to June 2019 after taking ethical approval from institutional ethical review committee and informed written consent from parents of patients. Confidentiality of the data was maintained and it was assured that no harm to study participants is done. A total of 108 term neonates with moderate to severe HIE presenting >6 hours of life were included. Preterm infants, major congenital anomaly and overt bleeding were excluded. Then selected patients were placed randomly into Group A (hypothermia group) & Group B (conservative group), by using lottery method. Outcome variable like mortality within 1st week was noted. There was no conflict of interest in the study and funding was done by the authors. Results: The mean age of patients in group A was 17.69 ± 6.68 hours and in group B was 17.60 ± 6.65 hours. Out of 108 patients, 62 (57.41%) were males and 46 (42.59%) were females with male to female ration of 1.3:1. There was mortality within one week (short term outcome) in 07 (12.96%) patients in Group A (hypothermia group) while in Group B (conservative group), it was seen in 16 (29.63%) patients. Conclusion: This study concluded that there is benefit of therapeutic hypothermia in asphyxiated newborns after 6 hours of life and short term outcome is better after therapeutic hypothermia in asphyxiated newborns. Keywords: Asphyxia, Encephalopathy, Mortality, Cooling.